PERMAINAN TRADISIONAL PETAK UMPET PADA MATERI MENYUSUN KATA MENJADI KALIMAT SISWA KELAS 2 SD - Firda Cahya Maulidia; Cholifah Tur Rosidah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
ABSTRACT This research was prompted by the lack of engagement and suboptimal learning outcomes observed among grade 2 primary school students in their ability to construct sentences from words, caused by monotonous and less interactive learning methods. The focus of this research is to analyze the application of the traditional game method of hide and seek in Indonesian language learning, especially in composing words into sentences. The approach applied in this research is a descriptive-quantitative one. The researcher selected 30 grade 2 students from SDN Kenjeran 248 Surabaya as the sample, using observation, a questionnaire, and a pretest-posttest learning outcome test as data collection techniques. The findings of this study showed that students' activities increased significantly with a percentage of involvement of 82.14% in the “Very High” category. In addition, students' responses to the method were also positive, with 59.66% of students responding “Strongly Agree” and 39.67% of students responding “Agree.” In terms of learning outcomes, there was an increase in students' average scores from pretest to posttest with a 90% completeness rate, compared to only 20% before the application of the method. Thus, the hide-and-seek game method proved effective in encouraging students' involvement, interest, and learning outcomes in composing words into sentences. Keywords: Traditional Games, Hide-and-Seek, Arranging Words, Sentences ABSTRAK Penelitian ini didorong oleh kurangnya keterlibatan dan hasil belajar yang kurang optimal yang diamati di antara siswa kelas 2 SD dalam kemampuan mereka menyusun kalimat dari kata-kata, yang disebabkan oleh metode pembelajaran yang monoton dan kurang interaktif. Fokus dari penelitian ini untuk menganalisis penerapan metode permainan tradisional petak umpet dalam pembelajaran Bahasa Indonesia, khususnya pada materi menyusun kata menjadi kalimat. Pendekatan yang diterapkan dalam penelitian ini adalah pendekatan kuantitatif deskriptif. Peneliti menetapkan 30 siswa kelas 2 SDN Kenjeran 248 Surabaya sebagai sampel dengan observasi, angket, dan tes hasil belajar pretest posttest sebagai teknik untuk mengumpulkan data. Temuan dari penelitian ini memperlihatkan bahwa aktivitas siswa meningkat secara signifikan dengan persentase keterlibatan sebesar 82,14% dalam kategori